Paghubad sa huwad isang pagsusuri sa pagkaepiko ng epicseryeng Amaya - Yalung, Denise Michelle Robielos 1991-; Guieb, Eulalio III R. (Quezon City University of the Philippines Diliman, 2012)
"This study is an analysis of the epic characteristics of the epicserye Amaya and how it used Philippine pre-colonial history and culture to make the show commercially viable. By using textual analysis, this study analyzed if the epicserye Amaya possesses the characteristics of our folk epic. It compared the narrative and themes of the folk epic Labaw Donggon and that of the epicserye Amaya using Structuralism. Since the show also claims to be based in some historical facts, this study also looked at some aspects of pre-colonial culture that have some significance to the narrative, and examined its historical accuracy. This study also examined the different production elements such as costume and make-up of the characters, production design, and language used in Amaya that showcase pre-colonial culture. It analyzed the representation of the said culture made by Amaya. This study then identified the various production and promotional strategies used by Amaya to make pre-colonial history and culture and the drama program commercially viable. Guided by Edward Said's Orientalism and Arnold Azurin's essay Mga Katiwalian sa ating Kamalayan Tungkol sa Kaalamang Bayan, this study critiqued how the show used pre-colonial history and culture to sell the show to its audiences."
Vita.
Undergraduate thesis
Keywords: Character and characteristics on television program; Amaya (Television program) -- Philippines).; Television series -- Content analysis (Communication) -- Philippines